Psychological Impact of Social Media Addiction on Interpersonal Relationships in Pakistan - Ahmed, Mahnoor (International Journal of Psychology, 2023)
Purpose: The aim of the study was to investigate the psychological impact of social media addiction on interpersonal relationships. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Social media addiction profoundly impacts interpersonal relationships, leading to heightened loneliness and diminished relationship satisfaction. Conflict and communication issues often arise, as excessive social media use can lead to neglect of face-to-face interactions and misunderstandings. Additionally, social comparison and lower self-esteem are common among those addicted to social media, further straining interpersonal connections. Addressing social media addiction is crucial for fostering healthier and more fulfilling relationships in the digital age. Unique Contribution to Theory, Practice and Policy: Attachment Theory, Social Exchange Theory & Interpersonal Communication Theory may be used to anchor future studies on the psychological impact of social media addiction on interpersonal relationships. Practical interventions should be grounded in both empirical evidence and theoretical frameworks to effectively address the psychological consequences of social media addiction on interpersonal relationships. Policymakers play a crucial role in advocating for regulations and guidelines aimed at mitigating the negative impact of social media addiction on interpersonal relationships.